THE IMPACT OF PERCEIVED CSR ON CUSTOMER LOYALTY IN THE PERSONAL CARE PRODUCTS MARKET - Ovidiu I. MOISESCU (Studia Universitatis Babeş-Bolyai Negotia, 2015)
The current research investigates the impact of customers’ perceptions of corporate social responsibility (CSR) on their loyalty towards brands/companies in one of the largest Central-Eastern European country’s personal care products market. The paper reveals useful findings regarding the nature of the relationship between perceived CSR and customer loyalty in the specific socio-cultural and economic context of Central-Eastern European countries, and in the particular business sector of personal care products. A consumer survey was designed and implemented among a sample of 1462 personal care products companies’ customers from the urban area of Romania. Perceived CSR was quantified with the aid of 28 specific items, while another set of 6 items was utilized to measure customer loyalty. The results indicate that customers’ loyalty is not significantly influenced by how these perceive companies’ responsibilities with regard to their economic success, employees, or community development and social sponsorship. However, other perceptions of CSR have a significant and positive impact on loyalty, the most important, by far, being customers’ perceptions of companies’ responsibility towards their customers, followed by how customers perceive companies’ responsibilities towards public authorities, cultural sponsorship, and the environment. The paper has practical implications in what concerns the appropriate dosage and marketing communication of CSR in the Central-Eastern European personal care products market.